ANALISIS KONSEPTUAL EVALUASI KINERJA GURU DALAM PERSPEKTIF TEORITIS: SEBUAH STUDI LITERATUR REVIEW - Alkafi, Kurnia; Ibtihal, Aqila Azharrani; Mu'in, Abdul; Zohriah, Anis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Performance evaluation in educational institutions is a systematic process to assess the effectiveness of the role of educators and education personnel in achieving learning organizational goals, which includes the dimensions of planning, implementation, assessment, guidance, and additional quality-oriented tasks. The practice of performance evaluation has been proven to support the improvement of learning quality when the supervision instruments used have adequate reliability and the results are followed up as a basis for professional development, competency development, and improvement of teaching practices. This article discusses the basic concepts, objectives, methods, and tools of teacher performance evaluation with a library research approach that focuses on theoretical studies and empirical results from various academic literature. The analysis was carried out in a descriptive-qualitative manner using relevant primary and secondary sources, such as scientific journals, books, and education regulations in Indonesia. The discussion included the distinction between formative and summative evaluation, the role of the principal as a supervisor, and the importance of teachers' involvement in the professional reflection process. The literature synthesis shows that the success of performance evaluation is determined not only by the completeness of the instrument, but also by the consistency of implementation and follow-up of assessment results. Evaluations that are integrated with continuous competency development are able to encourage positive changes in school culture and improve the quality of education as a whole. Thus, this study emphasizes the importance of designing a performance evaluation system that is comprehensive, objective, and oriented towards the professional development of teachers in Indonesia.